Paradigma Pembaharuan Fikih dan Istinbath Hukum KH. Ali Yafie - Asmani, Jamal Ma'mur; Muarif, Ahmad Dalhar (Islamic Review: Jurnal Riset dan Kajian Keislaman, 2024)
KH. Ali Yafie is a great scholar of the archipelago who performs ijtihad in the field of classical fiqh with the paradigm and action of fiqh reform so as to give birth to concepts that are applicable to the modern world. This research aims to explain the study of legal istinbath conducted by KH. Ali Yafie in the renewal of fiqh. This research is a library research with a descriptive qualitative approach. Data collection is done through documentation and interviews. The data analysis technique uses Miles and Huberman data analysis through three stages, namely data reduction, data presentation, and conclusion drawing. The results of the study explain that KH Ali Yafie's style of istinbath law is istislahi-maqashidi which prioritizes the general propositions of sharia and prioritizes benefit. KH Ali Yafie's paradigm of thought reform revolves around the concepts of tajdid, ijtihad, fiqh development, and istishlah. These four concepts encourage the dynamization and contextualization of fiqh so that it can answer social problems contextually and solutively. Meanwhile, the product of KH Ali Yafie's fiqh thinking revolves around four aspects, namely worship, mu'amalah, munakahah, and jinayat.